Improving Erosion Resistance of Mine Tailings with EPS-aided Biocementation - Dubey, Anant; Polat, Pelin; Pring, Allan; Mukherjee, Abhijit; Carlos, Rodríguez-Navarro; Dhami, Navdeep Kaur (2024)
Mining is the backbone of the global economy. However, with the immense contribution to technological advancement and the economy, mining also puts the geoenvironment under great threat with its byproduct, termed Mine Tailings (MT). MT are often dumped in engineered dams for their safe disposal. However, prolonged exposure to the environment induces instability in the MT depositions, which is often initiated by erosion. The failures of MT dams that happened at (1). the Baia Mare Aurul gold mine in Northwestern Romania, resulting in a toxic cyanide spill in river Tisza (2000) and (2). the Brumadinho dam disaster in Brazil (2019), killing 270 people, are a few of the threatening examples. In this paper, we discuss the potential of microbially-aided stabilisation technology for improvement in the mechanical properties of mine tailings. The MT samples were obtained from local mining industries in Western Australia and treated with the extracellular polymeric substance (EPS)-producing ureolytic culture of Bacillus subtilis capable of microbially induced calcium carbonate precipitating (MICP) via spraying strategy in multiple stages to develop an erosion-resilient surficial crust after characterising the virgin MT for its physicochemical (pH, electrical conductivity, mineralogy, grain size) characteristics. The surficial strength characteristics of the developed crust were investigated using a needle penetrometer in dry and wet conditions considering field conditions. The hydraulic erosion resistance of the specimens was investigated using a pocket erodometer for the treated samples in wet conditions. The results demonstrate that the erosion resistance of the MT material improved drastically with EPS-aided biocemented MT specimens despite lesser strength and CaCO¬3 content than only MICP treatment. The results from the current study can provide alternate solutions to provide an additional layer of safety in the closure of Mine Tailings.